Graphene Derivatives and Graphene Composite Electrocatalysts for N2 Reduction Reaction. Issue 2 (16th November 2020) - Wang, Fei; Mao, Limin; Xie, Hongtao; Mao, Jian
Abstract : Ammonia (NH3 ) plays a key role in human society. The conventional Haber–Bosch process under high temperature and pressure is widely used to synthesize NH3, resulting in huge energy costs and serious environmental issues. At present, the electrochemical conversion of nitrogen (N2 ) and water (H2 O) into NH3 at ambient conditions is considered as a promising and alternative method, and electrocatalysts are critical for nitrogen reduction reaction (NRR) to realize NH3 synthesis. Graphene as an emerging 2D material has received significant attention in electrocatalysis NRR due to its unique properties such as high conductivity, specific surface area, a distinct 2D structure, and simplicity for modification. Herein, the electrochemical basis for NRR is provided including reactions in the NRR system, NRR mechanisms, criteria for NRR electrocatalysts (density functional theory and experiments), and verifying the nitrogen source and electrolytes. Then, the effect of doping (nonmetallic elements and single/dual metal atoms) and intrinsic defects on the NRR performance for graphene derivatives is reviewed, and the graphene composite electrocatalysts for NRR are summarized. Furthermore, deep sights and existing issues toward the further development of graphene derivatives and graphene composite electrocatalysts on NRR are discussed. Abstract : The recent advances on graphene derivatives and graphene composite nitrogen reduction reaction (NRR) electrocatalysts are summarized, and some perspective directions and existing issues are proposed in this field.